Reciprocal relationships between forest management and regional landscape structures: applying concepts from land system science to private forest management. Issue 2 (4th March 2019) - Munroe, Darla K.; Crandall, Mindy S.; Colocousis, Chris; Bell, Kathleen P.; Morzillo, Anita T.
ABSTRACT: Maintaining forest cover and function given large-scale changes in population distribution, infrastructure, and regional economies represents a formidable societal challenge. Land architecture assumes landscape structures are collective outcomes of land-use decision-making, including how individual decisions about forest management reflect local, regional, and global phenomena. Yet, gaps in systematic understanding of these cross-scale interactions persist. We argue that current research on enduring and emerging forest policy issues, including parcelization and multifunctionality, neglects how changing landscape conditions mediate land-use changes. We highlight potential mechanisms by which regional context enables or constrains decisions on private forest landholdings in the northeastern United States, examining relationships between land use and land management of private forest landholdings and landscape-level dynamics such as exurban development, management of public lands, tourism, employment and commuting, infrastructure, and extraction. We describe an expanded set of regional landscape structures and social systems that shape and are shaped by land-use decision-making.